Strategic decision-making logics, entrepreneurial capability and opportunity exploitation in high-tech new ventures - Guo, Runping (Journal of Business Economics and Management, 2018)
This paper aims at exploring the influences of effectuation and causation on opportunity exploitation in high-tech new ventures and the mediating role of entrepreneurial capability by integrating effectuation theory and a perspective of entrepreneurial capability. The data was collected from entrepreneurs and top executives in high-tech new ventures through an interview survey instrument implemented in China. Factor analysis and multivariate linear regressions were run to test the hypotheses. The Baron and Kenny (1986) mediation model assessment procedure was used to analyze the data. The empirical analysis results of 176 Chinese high-tech new ventures indicate that both effectuation and causation have positive effects on opportunity exploitation and that entrepreneurial capability plays a fully mediating role in the relationship between strategic decision logic and opportunity exploitation. It is also found that in the context of China’s transition economy, the interaction effect between effectuation and causation on opportunity exploitation and entrepreneurial capability is insignificant. The research furthers the development of effectuation theory and enriches current literature on entrepreneurial capability by linking strategic decision-making logics to entrepreneurial capability and opportunity exploitation systematically. Moreover, the research has significant managerial implications for high-tech entrepreneurial practices, particularly in transition economies.